ACTIVE TEACHING-LEARNING METHODOLOGIES: experiences of applicable practices in technical education integrated focusing in the classes dynamization - Regattieri, Silvia Maria Alvim; Donadon, Maria Leonor Beneli (Revista Interface Tecnológica, 2020)
The experiences of innovated applicable practices has as focus the share of simple activities that were developed and reported as positive by students and teachers of Integrated Technical Education for High School (ITEHS). Considering the profile of technical education integrated to high school as something recent and still little explored in articles and events, the proposal to expose activities related to the public and to update part of the existing gap on the theme were the main motivations for the development of the work. The qualitative methodology was addressed in the development of interdisciplinary practices, being still bibliographic due to the articles, books, theses and journals applied in the foundation of the theme. The results obtained showed to be promising, being shared in external events and in the school unit, validating the approximation of disciplines of the common axis to those of technical specificity through active methodologies.